2017
DOI: 10.1016/j.aquaculture.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Paternal contribution to development: Sperm genetic damage and repair in fish

Abstract: In this review we provide an overview of the components of the spermatozoa playing an important role in reproductive success beyond fertilization, showing the relationship between the integrity of the diverse elements and the development of a healthy offspring. The present knowledge about fish sperm chromatin organization, epigenetic modifications of DNA and histones and sperm-borne RNAs, essential in controlling embryo development, is summarized, pointing out the possibility of using specific genes or transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 188 publications
0
29
0
15
Order By: Relevance
“…This method, used in studies involving the cryopreservation of human sperm, has been applied to detect lesions in genes that are key to the fertilization and early development of human embryos. Additionally, lesions have been quantified in specific genes in the primordial germ cells (PGCs) of zebrafish (Cart on-Garc ıa et al 2013; Gonz alez-Rojo et al 2014;Herr aez et al 2017).…”
Section: Effects Of Cryopreservation On Dna Quality and Gene Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…This method, used in studies involving the cryopreservation of human sperm, has been applied to detect lesions in genes that are key to the fertilization and early development of human embryos. Additionally, lesions have been quantified in specific genes in the primordial germ cells (PGCs) of zebrafish (Cart on-Garc ıa et al 2013; Gonz alez-Rojo et al 2014;Herr aez et al 2017).…”
Section: Effects Of Cryopreservation On Dna Quality and Gene Expressionmentioning
confidence: 99%
“…It has been used to increase the longevity of spermatozoa for periods extending to years (Betsy & Kumar ); however, it can cause extensive cellular and molecular damage, not yet studied in full, leading to a reduction in sperm quality and an increased rate of malformed embryos (Herráez et al . ). It has been shown that cryopreservation alters structural and physiological components of cells, specifically affecting plasma membrane integrity, mitochondrial membrane potential (ΔΨm) and enzyme activity; while production of free radicals (ROS) increases and ATP concentrations are disrupted (Figueroa et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies suggested that the drastic changes occurring during freezing and thawing may affect the DNA of cryopreserved spermatozoa (Labbé et al, 2017;Pérez-Cerezales et al, 2010). Furthermore, the use of methylated cryoprotectants is known to induce the production of reactive oxygen species (ROS) that can cause several damages, such as cytosine methylation in fish spermatozoa DNA (Kawai et al, 2010), which is one of the principal epigenetic mechanisms (Bird, 2002), and have been suggested to be a good indicator for sperm quality (Herráez et al, 2017), affecting consequently the success of a cryopreservation protocol. In this comparative study, Herranz-Jusdado et al (2019a) showed that the protocol using methanol, initially developed by the Hungarian group (Müller et al, 2012;Szabó et al, 2005), was better in terms of higher spermatozoa viability and motility than the protocol with DMSO developed by the Spanish group (Asturiano et al, 2016;Peñaranda et al, 2009).…”
Section: European Eel Sperm Cryopreservationmentioning
confidence: 99%